2018
DOI: 10.3748/wjg.v24.i45.5131
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal paracentesis drainage ameliorates severe acute pancreatitis in rats by regulating the polarization of peritoneal macrophages

Abstract: AIMTo investigate the role of peritoneal macrophage (PM) polarization in the therapeutic effect of abdominal paracentesis drainage (APD) on severe acute pancreatitis (SAP).METHODSSAP was induced by 5% Na-taurocholate retrograde injection in Sprague-Dawley rats. APD was performed by inserting a drainage tube with a vacuum ball into the lower right abdomen of the rats immediately after the induction of SAP. To verify the effect of APD on macrophages, PMs were isolated and cultured in an environment, with the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…The method of model preparation is similar to that we previously reported (Liu et al, 2018). Briefly, mice were randomly divided into control group and SAP group and anesthetized with 5% isoflurane (via induction box) prior to surgery.…”
Section: Preparation Of Sap Modelmentioning
confidence: 99%
“…The method of model preparation is similar to that we previously reported (Liu et al, 2018). Briefly, mice were randomly divided into control group and SAP group and anesthetized with 5% isoflurane (via induction box) prior to surgery.…”
Section: Preparation Of Sap Modelmentioning
confidence: 99%
“…After puncture needle and arterial clip were removed, the model was successfully constructed following the closure of abdomen. In APD group, a drainage tube with vacuum bulb was implanted in its right lower abdomen immediately after SAP induction [10]. No operation was performed in the SO group except abdominal opening and closing.…”
Section: Animal and Experimental Designmentioning
confidence: 99%
“…toxic substances such as tumor necrosis factor, interleukin, endotoxin and so on [2][3][4][5]. Our previous clinical and experimental studies showed that abdominal paracentesis drainage (APD) attenuated the outcomes of SAP safely and effectively through removing PAAF [6][7][8][9][10]. However, little is known about the underlying mechanisms responsible for APD treatment for SAP.…”
Section: Introductionmentioning
confidence: 99%
“…Since the polarization status of macrophages is related to the progression and severity of AP, many researchers have focused on the therapeutic effect of regulating the polarization status of macrophages on AP 48 , 91 , 121 , 122 . It is generally accepted that abdominal paracentesis drainage (APD) can alleviate AP.…”
Section: Macrophagesmentioning
confidence: 99%